Liver-related long-term outcomes of alpha-glucosidase inhibitors in patients with diabetes and liver cirrhosis - Yen, Fu-Shun; Hou, Ming-Chih; Wei, James Cheng-Chung; Shih, Ying-Hsiu; Hsu, Chung Y.; Hsu, Chih-Cheng; Hwu, Chii-Min (Frontiers in Pharmacology, 2022)
Adequate management of diabetes in patients with liver cirrhosis can be challenging. We conducted this study to investigate the liver-related long-term outcomes of alpha-glucosidase inhibitors (AGIs) in patients with diabetes and cirrhosis. From National Health Insurance Research Database (NHIRD) in Taiwan, we recruited propensity-score matched AGI users and nonusers from a cohort of type 2 diabetes mellitus (T2DM) with compensated liver cirrhosis between January 1, 2000, and December 31, 2017, and followed them until December 31, 2018. Cox proportional hazards models with robust sandwich standard error estimates were used to assess the risk of main outcomes for AGI users versus nonusers. The incidence rates of mortality during follow-up were 65.56 vs 96.06 per 1000 patient-years for AGI users and nonusers, respectively. The multivariable-adjusted model shows that AGI users had significantly lower risks of all-cause mortality (aHR 0.63, 95% CI 0.56-0.71), hepatocellular carcinoma (aHR 0.55, 95% CI 0.46-0.67), decompensated cirrhosis (aHR 0.74 95% CI 0.63-0.87), hepatic encephalopathy (aHR 0.72, 95% CI 0.60-0.87), and hepatic failure (aHR 0.74, 95% CI 0.62-0.88) than AGI nonusers. Patients who received AGIs for a cumulative duration of more than 364 days had significantly lower risks of these outcomes than nonusers. AGI use was associated with a lower risk of mortality, hepatocellular carcinoma, decompensated cirrhosis, and hepatic failure in patients with diabetes and compensated cirrhosis. AGIs may be useful for the management of diabetes in patients with compensated liver cirrhosis. Large-scale prospective studies are required to verify our results.